2014
DOI: 10.1021/ct4007037
|View full text |Cite
|
Sign up to set email alerts
|

Computing Clinically Relevant Binding Free Energies of HIV-1 Protease Inhibitors

Abstract: The use of molecular simulation to estimate the strength of macromolecular binding free energies is becoming increasingly widespread, with goals ranging from lead optimization and enrichment in drug discovery to personalizing or stratifying treatment regimes. In order to realize the potential of such approaches to predict new results, not merely to explain previous experimental findings, it is necessary that the methods used are reliable and accurate, and that their limitations are thoroughly understood. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
180
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(195 citation statements)
references
References 55 publications
13
180
0
Order By: Relevance
“…The MM-PBSA analyses of the binding energies showed lower energies for the AKR1B10-ligand complexes using hit 1, hit 2, and hit 3 as the ligand and the highest binding affinities due to the presence of hydrogen bonding and hydrophobic interactions in each of these complexes. The free energy calculations using MM/PBSA method have shown to produce reliable and reproducible predictions of binding affinity that could be used in drug discovery and personalized medicine applications [48] . It can be helpful to rank the lead compounds according to their predicted affinities to the target and this information may be used to guide molecular design and synthesis [49] .…”
Section: Discussionmentioning
confidence: 99%
“…The MM-PBSA analyses of the binding energies showed lower energies for the AKR1B10-ligand complexes using hit 1, hit 2, and hit 3 as the ligand and the highest binding affinities due to the presence of hydrogen bonding and hydrophobic interactions in each of these complexes. The free energy calculations using MM/PBSA method have shown to produce reliable and reproducible predictions of binding affinity that could be used in drug discovery and personalized medicine applications [48] . It can be helpful to rank the lead compounds according to their predicted affinities to the target and this information may be used to guide molecular design and synthesis [49] .…”
Section: Discussionmentioning
confidence: 99%
“…A sufficient number of replicas is needed to ensue full error control and hence reproducibility. 50 replica ensembles are used in this study, the same size we have used in our previous studies, although the study on HIV-1 protease inhibitors indicated that convergence can be reached for ensembles with a smaller number of replicas 14 One particularly interesting feature of the ESMACS protocol we report on here is the enhancement of predictions when we move from the so-called 1-trajectory to the 3-trajectory variant of the method, relaxing the assumption that the substrate and receptor protein sample similar conformations in both the free and bound states. The 1-trajectory method, in which the energies of protein-inhibitor complexes, receptor proteins and ligands/drugs/peptides are extracted from the MD trajectories of the complexes alone, has been used in virtually all MMPBSA studies in the literature.…”
Section: Enhancement Of Conformational Samplingmentioning
confidence: 99%
“…Our approach is based on a 'protocol' originally reported for estimating binding affinities of inhibitors to HIV-1 protease 14,19 . We call this protocol "enhanced sampling of molecular 7 dynamics with the approximation of continuum solvent" (ESMACS).…”
Section: Introductionmentioning
confidence: 99%
“…46,47 In order to gain further insight into the relative stability of our four oligomers, we have done MM-PBSA calculations of the oligomers allowing us to monitor their interactions 48 through calculating approximate binding free energies from molecular simulations. 49,50 While the MM-PBSA approach in general does not replicate the absolute binding free energy values, 51 we chose this approach because it allows one to calculate quickly an estimate for differences in the free energy of binding, and because it usually exhibits a good correlation with experimental data. 52 In the present study, the binding energy between the two β-sheets (that is between the pentamers that form the decamer) is estimated with the MM-PBSA methodology as implemented in AMBER12.…”
Section: Free Energies Of Wild Type and Iowa Aggregatesmentioning
confidence: 99%